2011
DOI: 10.4049/jimmunol.1100530
|View full text |Cite
|
Sign up to set email alerts
|

Segregated Regulatory CD39+CD4+ T Cell Function: TGF-β–Producing Foxp3− and IL-10–Producing Foxp3+ Cells Are Interdependent for Protection against Collagen-Induced Arthritis

Abstract: Oral immunization with a Salmonella vaccine vector expressing enterotoxigenic E. coli colonization factor antigen I (CFA/I) can protect against collagen-induced arthritis (CIA) by dampening IL-17 and IFN-γ via enhanced IL-4, IL-10, and TGF-β. To identify the responsible regulatory CD4+ T cells making the host refractory to CIA, Salmonella-CFA/I induced CD39+CD4+ T cells with enhanced apyrase activity relative to Salmonella vector-immunized mice. Adoptive transfer of vaccine-induced CD39+CD4+ T cells into CIA m… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

6
71
0
3

Year Published

2012
2012
2021
2021

Publication Types

Select...
9

Relationship

1
8

Authors

Journals

citations
Cited by 38 publications
(85 citation statements)
references
References 50 publications
(108 reference statements)
6
71
0
3
Order By: Relevance
“…17,[29][30][31][32][33][34][35] Our work and others show that within CD4 T cells, CD39 is a marker that delineates regulatory subsets independent of Foxp3. 36,37 It can be inferred that CD39 + CD4 T cells may comprise diverse regulatory subsets, including the canonical Foxp3 + CD4 Tregs, IL-10-secreting T regulatory type 1 (Tr1) cells and TGF-β-secreting T helper 3 (Th3) cells. The profile of chemokine receptors on CD39 + CD4 T cells suggests this postulation.…”
Section: Discussionmentioning
confidence: 99%
“…17,[29][30][31][32][33][34][35] Our work and others show that within CD4 T cells, CD39 is a marker that delineates regulatory subsets independent of Foxp3. 36,37 It can be inferred that CD39 + CD4 T cells may comprise diverse regulatory subsets, including the canonical Foxp3 + CD4 Tregs, IL-10-secreting T regulatory type 1 (Tr1) cells and TGF-β-secreting T helper 3 (Th3) cells. The profile of chemokine receptors on CD39 + CD4 T cells suggests this postulation.…”
Section: Discussionmentioning
confidence: 99%
“…It has been reported that CD39 + Foxp3 + CD4 Tregs but not CD39 − Foxp3 + CD4 Tregs can effectively suppress Th17 45 . However, several studies indicate that CD39 + CD4 T cell is in itself a regulatory subset regardless of Foxp3 46,47 . It is speculated that CD39 + CD4 T cell consists of both Foxp3 + Tregs and Tr1 cells.…”
Section: Discussionmentioning
confidence: 99%
“…FoxP3ϩCD39ϩ Treg cells are impaired in patients with multiple sclerosis (33). Conversely, the CD39ϩ Treg cell population expands during remission of multiple sclerosis and after antiinflammatory treatment in CIA (46,47). Moreover, a very recent study has shown that an efficient therapy based on stem cell adoptive transfer mostly depended on CD39/CD73 signals and partially on the induction of CD4ϩCD39ϩFoxP3ϩ Treg cells in CIA (48).…”
Section: Discussionmentioning
confidence: 99%